Neoliberal Elements in Canadian Teacher Education: Challenges and Possibilities - Portelli, John Peter; Oladi, Soudeh (Alberta Journal of Educational Research, 2019)
This article offers a critical reflection of the changes experienced in teacher education across Canada in light of the neoliberal impact on educational spaces. It also seeks to disrupt the neoliberal narrative and problematize a rationality that has permeated teacher education programs. The article maintains that the neoliberal agenda is incompatible with critical educational practices. As a mode of critical resistance to educational instrumentalism, the paper offers recommendations as part of its critique on the deleterious impact of neoliberalism. Cet article offre une réflexion critique des changements découlant de l’impact néolibéral sur les milieux éducatifs qui touchent la formation des enseignants partout au Canada. L’article veut également perturber la théorie néolibérale et problématiser une rationalité qui s’est infiltrée dans les programmes de formation des enseignants. L’article affirme que le programme néolibéral est incompatible avec des pratiques éducatives cruciales. Comme élément de sa critique de l’impact néfaste du néolibéralisme, l’article propose des recommandations en guise de moyens de résistance critique à l’instrumentalisme en éducation. Mots clés : néolibéralisme, formation des enseignants justice sociale, instrumentalisme